Design and Control of a Pneumatic Muscle Servo Drive Containing Its Own Pneumatic Muscles - Dawid Sebastian Pietrala; Pawel Andrzej Laski (Applied Sciences, 2022)
This article presents static and dynamic characteristics of artificial pneumatic muscles. The research stance and the methodology for their determination are described. A mathematical model of a pneumatic muscle has been proposed, having two inputs—the force generated by the muscle and the displacement of the muscle tip, and one output—the valve control voltage. The quality of object mapping was verified by a mathematical model for various trajectories. Then, the control system for the moment servo drive force was composed of two pneumatic muscles working in opposite directions connected by a toothed belt gear. The servo drive was verified and evaluated.